Sociodemographic profile of geriatric patients attending psychiatry department in a tertiary care center - Neupane, Bastabika; Pradhan, Sudarshan Narsingh; Sharma, Subash; Sharma Basnet, Rachana (Journal of Patan Academy of Health Sciences, 2024)
Introduction: With rise in life expectancy, the elderly population is increasing globally and in Nepal. With increasing age, medical and psychiatric co-morbidities have become a challenge. This study aimed to study sociodemographic profile and associated life stressors in geriatric population attending psychiatric unit in tertiary care center. Method: A hospital based cross-sectional study was conducted among 101 elderly patients and diagnosis was made as per ICD-10 DCR (Diagnostic Criteria for Research) criteria. PSLES (Presumptive Stressful Life Events Scale) was used to identify various stressful life events. Analysis of descriptive variable were done using MS Excel. Result: Study conducted among 101 elderly patients showed that most patients had depression 50(49.50%) and among 51 stressful events as per PSLES, 19 were present in participants. Among 50 patients diagnosed as depression, 7(14.00%) had mild, 39(78.00%) had moderate, 4(8.00%) had mild depression. Stressful life events were significantly associated with geriatric depression. Conclusion: It was seen that depression was the commonest diagnosis among the elderly people attending psychiatric outpatient clinic and stressful life events were present.